Isolasi dan identifikasi kapang Rhizopus pada tempe gude (Cajanus cajan L.) - Yuni Sine; Endang S. Soetarto (Fakultas Pertanian, Universitas Timor, 2018)
The research has been done to isolate Rhizopus mold in Pigeon pea tempeh, as it is known that Rhizopus is a very important mold in tempeh fermentation process. This study begins with the manufacture of tempeh using pigeon pea as a substrate, and then inoculated with molds of traditional inoculum (usar), incubated at room temperature for 48-72 hours. Mold that grows on pigeon pea isolated and identified by dilution methods and spread plates. The result showed that pigeon pea as growth substrate for Rhizopus sp. Pigeon pea tempeh’s molds was dominated by white-greyish molds and white grey brownish that identified similar to Rhizopus oligosporus.